A portable induction heating system for implanted prosthesis disinfection - Alvarez-Gariburo, Ignacio; Sarnago Andía, Héctor; Lucía Gil, Óscar; Acero Acero, Jesús; Burdío Pinilla, José Miguel (Jornada de Jóvenes Investigadores del I3A, 2023)
Prosthetic implants, such as knee or hip prostheses, have significantly improved the wellbeing of citizens with articulation problems. However, there are still significant challenges in these procedures, being recurring infections one of the most challenging. In this context, hyperthermia has been studied as an effective alternative to antibiotics for biofilm eradication. Among the different heating alternatives, induction heating arises as the idoneous for this application due to its contactless nature and the metallic alloys used in prosthesis. This papers details the design of a portable induction heating system for implanted prosthesis disinfection.